Folk music culture in the Lublin region in the conditions of socialist realism (1944-1956). Prolegomena - Kusto, Agata (Literatura Ludowa. Journal of Folklore and Popular Culture, 2021)
The article is devoted to selected issues of social and cultural life that had a significant impact on the folk music culture of the Lublin region during the period of socialist realism (1944-1956). At the beginning of the text the specifics of Polish cultural policy are determined, as well as the changes touching upon social culture in the countryside in the described period. Then the organizational structure of musical life in Lublin and the region is presented, in particular describing the amateur and professional movement and methods of promoting high culture. The further part of the text constitutes an attempt to define the attitudes of folk creators of culture towards the newly created requirements of socio-economic life in the Lublin province. In this context, the specifics of singing groups are presented, as well as the culture-forming activity of the Rural Housewives' Clubs, the functioning of folk universities and the undertaking of cultural initiatives within the created organizations and associations. The conclusion discusses the role of the individual figures of singers and musicians as depositories of traditions carried over generations as the core of the above initiatives.